Preterm Infants’ Weight Gain and Nutrition: Retrospective Study in a Top Indonesian Referral Hospital - Irianti, Dewi; Rustina, Yeni; Efendi, Defi (Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Background: Impairment of nutritional fulfillment is one of the problems that is often encountered in premature infants. Purpose: This study aims to determine the effect of the type of nutrition on the weight increase of premature babies.Methods: A retrospective study was conducted through a medical record review in a top national referral hospital, Indonesia. Total of 75 preterm infants divided into groups of 15 infants by nutrition type (100% BM, 75% BM, 50% BM, 25% BM, and 0% BM). Weight gain was assessed for 12 days through the patients’ medical records. Weighing observation was devided into four times: birth weight in day-1, day-4, day-8, and day-12. Subjects were recruited using consecutive sampling with the following criteria: preterm infants with chronological age > 7 days and weight > 1000 grams. Meanwhile, the exclusion criteria were preterm infants treated in the neonatal intensive care unit (NICU), preterm infants with medical diagnosis of hydrocephalus, sepsis, and congenital anomalies, conjoined twin babies. The general linear model-repeated measure was used to quantify the contrast of increases in infants’ body weight among groups for days 1-4; 4-8; and 8-12. Results: There were no significant differences between the five types of nutrients in terms of increase in the infants’ body weight in day 1-4 (p > 0,68); day 4-8 (p > 0,65); day 8-12 (p > 0,12). Conclusion: Although it not likely to accelerate the infant’s weight, mother’s own milk is still the first recommendation due to its immunity components, nutritional elements, and safety.